Anthropogenic Threats to Wild Cetacean Welfare and a Tool to Inform Policy in This Area - Nicol, Christine; Bejder, Lars; Green, Laura; Johnson, Craig; Keeling, Linda; Noren, Dawn; Van der Hoop, Julie; Simmonds, Mark (Frontiers in Veterinary Science, 2020)
Human activities and anthropogenic environmental changes are having a profound effect on biodiversity and the sustainability and health of many populations and species of wild mammals. There has been less attention devoted to the impact of human activities on the welfare of individual wild mammals, although ethical reasoning suggests that the welfare of an individual is important regardless of species abundance or population health. There is growing interest in developing methodologies and frameworks that could be used to obtain an overview of anthropogenic threats to animal welfare. This paper shows the steps taken to develop a functional welfare assessment tool for wild cetaceans (WATWC), via an iterative process involving input from a wide range of experts and stakeholders. Animal welfare is a multi-dimensional concept and the WATWC presented made use of the Five Domains model of animal welfare to ensure that all areas of potential welfare impact were considered. A pilot version of the tool was tested and then refined to improve functionality. We demonstrated that the refined version of the WATWC was useful to assess real-world impacts of human activity on Southern Resident killer whales. There was close within-scenario agreement between assessors as well as between-scenario differentiation of overall welfare impact. The current article discusses the challenges raised by assessing welfare in scenarios where objective data on cetacean behavioural and physiological responses are sparse, and proposes that the WATWC approach has value in identifying important information gaps and in contributing to policy decisions relating to human impacts on whales, dolphins and porpoises.